2017
DOI: 10.1556/1326.2017.00327
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phenolic compounds, antioxidant capacity and organic acids contents of Prunus domestica L., Prunus cerasifera Ehrh. and Prunus spinosa L. fruits by HPLC

Abstract: The important role of fruits in human health and nutrition has been better understood with the recent studies on biochemical contents of fruits having antioxidant properties. Being one of the similar studies, in this study, total antioxidant capacity (TAC), phenolic compound, organic acid, and vitamin C contents of three plum species (Prunus domestica L., Prunus cerasifera Ehrh., and Prunus spinosa L.) grown in Van locality (Turkey) were identified, and the correlation between the measured values was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 16 publications
2
33
2
Order By: Relevance
“…Taken together, the present study described the first time of isolation of the phenolic constituents from P. cerasifera Ldb leaves. Eleven phenolic acids including p-coumaric acid (1), caffeic acid (2), ferulic acid (3), chlorogenic acid (4), 3-Ocaffeoylquinic acid (5), 5-O-coumaroylquinic acid (6), 3-Ocaffeoylquinic acid methyl ester (7), chlorogenic acid methyl ester (8), 3-O-caffeoyl-5-O-coumaroylquinic acid or 3-Ocoumaroyl-5-O-caffeoylquinic acid (9), gallic acid (10), and protocatechuic acid (11) were identified. e current study pioneers to identify and report all the phenolic constituents from P. cerasifera Ldb leaves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the present study described the first time of isolation of the phenolic constituents from P. cerasifera Ldb leaves. Eleven phenolic acids including p-coumaric acid (1), caffeic acid (2), ferulic acid (3), chlorogenic acid (4), 3-Ocaffeoylquinic acid (5), 5-O-coumaroylquinic acid (6), 3-Ocaffeoylquinic acid methyl ester (7), chlorogenic acid methyl ester (8), 3-O-caffeoyl-5-O-coumaroylquinic acid or 3-Ocoumaroyl-5-O-caffeoylquinic acid (9), gallic acid (10), and protocatechuic acid (11) were identified. e current study pioneers to identify and report all the phenolic constituents from P. cerasifera Ldb leaves.…”
Section: Resultsmentioning
confidence: 99%
“…(vernacular name mirabalan) is native to the Tianshan area of the Xinjiang province and well liked by the community due to its higher nutrition values [1,3]. e genus Prunus have extensively been studied for their phytochemical screening and reported to contain different polyphenols and their derivatives [4][5][6][7][8][9][10][11]. Moreover, P. cerasifera is an endangered fruit species grown wild in Southern slopes of the Huicheng area in the Xianjiang province of China [12].…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous data on the biochemical properties of Prunus spinosa, the aboveground organs of this plant are rich in biologically active compounds. The content of cyanogenic glycoside prunasin in sprouts is in the range of 131-691 mg/100 g DM (Levon et al, 2007), catechin content in fresh fruits -78.5 mg/100 g DM (Mustafaeva, 2013), vitamin C -25.5 mg/100 g DM (Celik et al, 2017). Eight flavonoids were isolated from the flowers of Prunus spinosa: kaempferol, quercetin, kaempferol 3-O-alpha-L-arabinofuranoside, quercetin 3-O-alpha-L-arabinofuranoside, kaempferol 3-O-alpha-L-ramnopyranoside, kaempferol 7-O-alpha-L-ramnopyranoside, kaempferol 3-O-beta-D-xylopyranoside, kaempferol 3-O-(2''-E-p-coumaroyl)-alpha-L-arabinofuranoside.…”
Section: Resultsmentioning
confidence: 99%
“…Also, in the Pinacho study, gallic acid was identified in the concentration of 0.2226 mg/100g and caffeic acid in the concentration of 0.1272 mg/100g [17]. The analysis of polyphenolic compounds by Celik et al showed the presence of chlorogenic acid at 1.2985 mg/100g [23]. The differences between polyphenol concentrations mentioned above may be linked to the pedoclimatic conditions.…”
Section: Identification and Quantification Of Polyphenols By Hplc Anamentioning
confidence: 93%